Best Practices on the Integration of Usability at the Organizational Level: A Review (LACCEI, 2024)
This article analyzes existing practices or guides in the literature for software organizations to improve the usability of their applications. The selected research method is the synthesis of qualitative data through a thematic synthesis. In this research, different recommendations were recovered to achieve the incorporation of usability at the organizational level, mainly derived from case studies. As a result, 13 topics grouped into 5 higher order topics have been obtained. These topics summarize the important and necessary aspects, to not only achieve usable software projects as a result, but to that usability is present as part of the essence of the organization. One of the main contributions of this work is the model of interrelation between the themes identified in this work. This model presents the existing knowledge in the literature on good practices to integrate usability at the corporate level.